Using virtual simulations with avatars to train pre-service special needs teachers’ relational competence: possibilities and limitations - Sofia Lindberg (Cogent Education)
This study aims to explore the use of virtual simulations with avatars in the training of pre-service special needs teachers’ (PsSNT) relational competence. I examine the possibilities and limitations of relational competence identified by PsSNTs when they describe their experiences of interacting with avatars. The study sample comprised twenty PsSNTs who participated in simulations and video interviews. The Relational Competence Model (RCM) was used to analyze how relational competence manifests in the interactions between PsSNTs and avatars. Two data sources were used: screen observations and focus group interviews. The focus group interviews were analyzed using a thematic analysis. The results show that there are both possibilities and limitations related to training PsSNTs’ relational competence using virtual simulations with avatars. This study suggests that avatar technology can be a valuable tool for training relational competence in Teacher Education (TE) and Special Education Teacher Training (SETT). The study’s contribution to research on relational competence and virtual simulations and the findings’ implications for TE and SETT are discussed in detail.